PENERAPAN SISTEM KEAMANAN JARINGAN SMK NEGERI 1 INDRALAYA UTARA DENGAN MIKROTIK - Suryayusra, Suryayusra ; Solikin, Imam ; Ulfa, Maria (JURNAL ILMIAH MATRIK, 2017)
Abstract: SMK Negeri 1 Indralaya Utara is a public vocational high school that has implemented internet network as part of all activities and learning media. Computer network security system using LAN and WLAN management has implemented network security applications on access point on the network, some problems that often occur network performance becomes slow and sometimes not connected properly. It caused by several factors such as intruder attacks from the local network or the internet or viruses that exist on each computer used. From these problems will be developed existing network security system to improve network quality and performance. Mikrotik router is one solution that will be used in this research because mikrotik router has features of network security system complete and easy to use. Implementation of network security system with firewall and web proxy on network, very help network administrator in arranging access of network user in using internet service. Keywords: Network Security System, Mikrotik, Computer Network